An innovative methodology for measurement of stress distribution of inflatable membrane structures. (23rd December 2015) - Zhao, Bing; Chen, Wujun; Hu, Jianhui; Chen, Jianwen; Qiu, Zhenyu; Zhou, Jinyu; Gao, Chengjun
Abstract: The inflatable membrane structure has been widely used in the fields of civil building, industrial building, airship, super pressure balloon and spacecraft. It is important to measure the stress distribution of the inflatable membrane structure because it influences the safety of the structural design. This paper presents an innovative methodology for the measurement and determination of the stress distribution of the inflatable membrane structure under different internal pressures, combining photogrammetry and the force-finding method. The shape of the inflatable membrane structure is maintained by the use of pressurized air, and the internal pressure is controlled and measured by means of an automatic pressure control system. The 3D coordinates of the marking points pasted on the membrane surface are acquired by three photographs captured from three cameras based on photogrammetry. After digitizing the markings on the photographs, the 3D curved surfaces are rebuilt. The continuous membrane surfaces are discretized into quadrilateral mesh and simulated by membrane links to calculate the stress distributions using the force-finding method. The internal pressure is simplified to the external node forces in the normal direction according to the contributory area of the node. Once the geometryx, the external forcer and the topologyC are obtained, the unknown force densitiesq in each link can be determined. Therefore, the stress distributions of the inflatable membrane structure can be calculated, combining the linear adjustment theory and the force density method based on the force equilibrium of inflated internal pressure and membrane internal force without considering the mechanical properties of the constitutive material. As the use of the inflatable membrane structure is attractive in the field of civil building, an ethylene-tetrafluoroethylene (ETFE) cushion is used with the measurement model to validate the proposed methodology. The comparisons between the obtained results and numerical simulation for the inflation process of the ETFE cushion are performed, and the strong agreements demonstrate that the proposed methodology is feasible and accurate.